THE LEXICAL – SEMANTIC FEATURES OF THE GENERAL SEMANTIC NOUN UNITS “BELIEF” ARE DESCRIBED (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the spiritual group “Faith” of the field of “Spirituality” and its role in the language system, the relationship of lexemes within this group. The lexical – semantic features of the general semantic noun units “Belief” are described.